Remainder and Factor Theorem Proof | Remainder and Factor Theorem Test
Contents
In this page given definition and proof for Remainder Theorem and Factor Theorem and also provided application of remainder theorem and factor theorem
Statement of Remainder Theorem:
Let f(x) be any polynomial of degree greater than or equal to one and let ‘ a‘ be any number. If f(x) is divided by the linear polynomial (x-a) then the remainder is f(a).
Remainder Theorem Proof:
Let f(x) be any polynomial with degree greater than or equal to 1.
Further suppose that when f(x) is divided by a linear polynomial p(x) = ( x -a), the quotient is q(x) and the remainder is r(x).
In other words , f(x) and p(x) are two polynomials such that the degree of f(x) degree of p(x) and p(x) 0 then we can find polynomials q(x) and r(x) such that, where r(x) = 0 or degree of r(x) < degree of g(x).
By division algorithm
f(x) = p(x) . q(x) + r(x)
∴ f(x) = (x-a) . q(x) + r(x) [ here p(x) = x – a ]
Since degree of p(x) = (x-a) is 1 and degree of r(x) < degree of (x-a)
∴ Degree of r(x) = 0
This implies that r(x) is a constant , say ‘ k ‘
So, for every real value of x, r(x) = k.
Therefore f(x) = ( x-a) . q(x) + k
If x = a,
then f(a) = (a-a) . q(a) + k = 0 + k = k
Hence the remainder when f(x) is divided by the linear polynomial (x-a) is f(a).
Statement of Factor Theorem:
If f(x) is a polynomial of degree n 1 and ‘ a ‘ is any real number then
- (x -a) is a factor of f(x), if f(a) = 0.
- and its converse ” if (x-a) is a factor of a polynomial f(x) then f(a) = 0 “
Factor Theorem Proof:
Given that f(x) is a polynomial of degree n 1 by reminder theorem.
f(x) = ( x-a) . q(x) + f(a) . . . . . . . . . . . equation ‘A ‘
1 . Suppose f(a) = 0
then equation ‘A’ f(x) = ( x-a) . q(x) + 0 = ( x-a) . q(x)
Which shows that ( x-a) is a factor of f(x). Hence proved
2 . Conversely suppose that (x-a) is a factor of f(x).
This implies that f(x) = ( x-a) . q(x) for some polynomial q(x).
∴ f(a) = ( a-a) . q(a) = 0.
Hence f(a) = 0 when (x-a) is a factor of f(x).
The factor theorem simply say that If a polynomial f(x) is divided by p(x) leaves remainder zero then p(x) is factor of f(x)
Application of remainder theorem
Suppose f(x)is a polynomial of degree 1 then
- The remainder when f(x) is divided by ( x+a) is f(-a)
- The remainder when f(x) is divided by ( ax +b) is
- The remainder when f(x) is divided by ( ax – b) is
Application of factor theorem
( x – a) is a factor of x^{n} – a^{n } for any n N (any natural number)
( x + a) is a factor of x^{n} – a^{n} if n is even number
( x + a) is a factor of x^{n} + a^{n} if n is odd number
Application of factor theorem for quadratic polynomials:
Consider a quadratic polynomial ax^{2} + bx + c ( where a 0 and a,b & c are constants )
Now let its factors be (px + q) & (rx + s)
Then ax^{2} + bx + c = (px + q) (rx + s) = prx^{2} + (ps + qr)x + qs.
Comparing the coefficients of x^{2}, x and constants, we get that
- a = pr
- b = ps + qr
- c = qs
This shows that ‘ b ‘ is the sum of two numbers ‘ ps ‘ & ‘ qr ‘ .
Whose product is (ps) (qr) = pr x qs = ac
Therefore, to factorise ax^{2} + bx + c , we have to write ‘ b ‘ as the sum of two numbers whose product is ‘ ac ‘
Remainder and Factor Theorem Practice
Example – 1 : Find the remainder when x^{3} – 2x^{2} + 5x + 8 is divided by x + 1
Solution: Let f(x) = x^{3} – 2x^{2} + 5x + 8
Now divisor = x + 1 , its zero is ‘ -1 ‘
By the remainder theorem, the required remainder = f( -1)
put x = -1 in above equation then we get
f (-1) = (-1)^{3} – 2(-1)^{2} + 5(-1) + 8 = – 1 – 2 – 5 + 8 = 0
Remainder = 0
Example – 2 : Find the remainder when 2x^{3} + 4x^{2} – 8x + 4 is divided by 2x + 1
Solution: Let f(x) =2x^{3} + 4x^{2} – 8x + 4
Now divisor = 2x + 1 , its zero is ‘ -1/2 ‘
By the remainder theorem, the required remainder =
put x = -1/2 in above equation then we get
= 2(-1/2)^{3} + 4(-1/2)^{2} – 8(-1/2) + 4 = -(1/4) + 1 + 4 + 4 = 39/4
Remainder = 39/4
Example – 3 : Find the remainder when x^{3} – px^{2} + 6x – p is divided by (x -p)
Solution: Let f(x) = x^{3} – px^{2} + 6x – p
Now divisor q(x) = x -p, its zero is ‘ p ‘
According to remainder theorem, when f(x) is divided by q(x) is f(p)
put x = p in above equation then we get
f(p) = p^{3} – p .p^{2} + 6p – p = 5p
Remainder = 5p.
Example – 4 : Determine whether (x +2) is a factor of x^{3} – 4x^{2} – 4x + 16
Solution: Let f(x) = x^{3} – 4x^{2} – 4x + 16
According to factor theorem, ( x+ 2) will be factor of f(x) if f(-2) = 0
put x = -2 in above equation then we get
f(-2) = (-2)^{3} – 4(-2)^{2} – 4(-2) + 16 = – 8 – 16 + 8 + 16 = 0
Hence ( x+2 ) is a factor of x^{3} – 4x^{2} – 4x + 16 .
Example – 5 : Find the values of p & q such that the polynomial x^{3} – px^{2} – 13x + q has ( x – 1) and ( x + 3 ) as factors.
Solution: Let f(x) = x^{3} – px^{2} – 13x + q
Since ( x – 1) is a factor of f(x). This implies f(1) = 0
i.e (1)^{3} – p(1)^{2} – 13(1) + q = 0
– p + q = 12 . . . . . . . . eq.n I
Also since (x +3) is a factor of f(x).
This implies f(-3) = (-3)^{3} – p(-3)^{2} – 13(-3) + q = 0
-27 – 9p + 39 + q = 0
– 9p + q = -12 . . . . . . . . eq.n II
Subtract equation from II to I
– 8p = – 24
p = 3
Now the value of ‘ p substitute in equation – I then
q = 12 + 3 = 15
Therefore we get p = 3 and q = 15
Hi friends Thanks for reading. I Hope you liked this article ” remainder and factor theorem tutorial”. Give feed back, comments and please don’t forget to share it.
Related Topics :
Remainder Theorem Aptitude Exercise – I
Remainder Theorem Aptitude Exercise – II
Finding Last Digit of any Number with Power
Shortcut to Find Number of Factors of a Number
Main Pages
Topics in Quantitative aptitude math for all types of exams
Shortcut Math Tricks for helpful to improve speed in all calculations
2 thoughts on “State and Prove Remainder Theorem and Factor Theorem | Polynomials”
Jeetendra Badamundi
(January 15, 2019 - 5:01 pm)Well defined
sivaalluri
(January 22, 2019 - 2:01 pm)Thank you Jeetendra Badamundi